Talousrikosten tutkinta - Vuorinen, Sami. (Helsinki : Oikeuspoliittinen tutkimuslaitos, 2002)
Summary (s. 157-163): Investigating cases of economic crime.
Keywords: talousrikokset; esitutkinta; tutkimus; white collar crime; crime; economics; investigations (law enforcement)